Diversity of Beneficial Insect in Corn Plantation at West Sumatra - Martinus Abuzar; Ujang Khairul; Hasmiandy Hamid (Jurnal Perlindungan Tanaman Indonesia, 2021)
Corn is one of Indonesia's agricultural products with economical and strategic value and many potential to develop, such as carbohydrates and protein sources. There are two types of beneficial insects in corn production: predators and parasitoids. This study aims to identify the diversity of beneficial insects in corn plantations. This study was conducted from May to September 2019 in four different locations across West Sumatra, namely Padang Pariaman, West Pasaman, Pesisir Selatan, Solok Regencies. Identification of beneficial insects was made in Entomology Laboratory, Faculty of Agriculture, Andalas University. This study adopted a purposive sampling method using 20 sweeps of sweep nets, following a transect line of cornfields. The result showed five orders, 34 families, 101 morphospecies, and 747 beneficial insects in all locations. The diversity in each location varies from high, medium, and low. In all areas, the diversity index was high, with the criteria of ≥ 2.90, implying that the condition of the community structure was very stable. From the evenness index analysis, three locations were classified as high, and the other one was moderate. These three sites were Padang Pariaman, West Pasaman, and Solok, with criteria of ≥ 0.90 and very stable distribution conditions.